Characteristic of Cu–Al2O3 composites prepared by internal oxidation–remelting solidification. Issue 2 (21st September 2017) - Li, Xin; Ren, Fengzhang; Tian, Baohong; Xiong, Yi; Wei, Shizhong
Abstract : Copper (Cu)–aluminum oxide (Al2 O3 ) composite sheets were prepared by internal oxidation of copper–aluminum (Al) alloy sheets with different aluminum contents. For the same internal oxidation temperature and time, the microstructures and properties of the copper–aluminum oxide composite sheets were compared. In order to prepare a densified copper–aluminum oxide bulk composite, the remelting solidification method of copper–aluminum oxide composite sheets was tried. The results show that with increasing aluminum content, the internal grains become coarser and the depth of the internal oxidation layer becomes narrower for the same internal oxidation time. The hardness of internal oxidation layer gradually decreases from the surface to the inner layers. For the same internal oxidation time, the higher the aluminum content, the higher the hardness of the internal oxidation layer at the same depth. Aluminum oxide particles inside the molten composite sheets are more likely aggregate and rise during the remelting–solidification process. The preparation of copper–aluminum oxide bulk composites by the internal oxidation–remelting solidification method is infeasible.